Determinação de evapotranspiração do consorcio feijão-milho-algodão pelo método do balanço hídrico e através de formulas empíricas sob regime de irrigação por sulcos - Marca, Oneide Rodrigues (1985)
This work was conducted at the "Curu Valley Experimental Farm" of the Federal University of Ceara, in the Northeast Brazil. The water balance method, according to ROSE & STERN (1967), was used to determine the evapotranspiration (ETA) of intercropped cowpeas, corn and cotton, for the life cycle of the crops, under irrigation, in an alluvial eutrofic soil. [...]